Ubiquitination in plant nutrient utilization - Yates, Gary; Sadanandom, Ari (Frontiers in Plant Science, 2013)
Ubiquitin is well established as a major modifier of signaling in eukaryotes. However the extent to which plants rely on ubiquitin for regulating nutrient uptake is still in its infancy. The main characteristic of ubiquitination is the conjugation of ubiquitin onto lysine residues of acceptor proteins. In most cases the targeted protein is rapidly degraded by the 26S proteasome, the major proteolysis machinery in eukaryotic cells. The Ubiquitin-Proteasome System is responsible for removing most abnormal peptides and short-lived cellular regulators, which, in turn, control many processes. This allows cells to respond rapidly to intracellular signals and changing environmental conditions. This perspective will discuss how plants utilize ubiquitin conjugation for sensing environmental nutrient levels. We will highlight recent advances in understanding how ubiquitin aids nutrient homeostasis by affecting the trafficking of membrane bound transporters. Given the overrepresentation of genes encoding ubiquitin-metabolizing enzymes in plants, intracellular signaling events regulated by ubiquitin that lead to transcriptional responses due to nutrient starvation is an under explored area ripe for new discoveries.